2019
DOI: 10.1101/780379
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

HYPK scaffolds the Nedd8 and LC3 proteins to initiate formation of autophagosome around polyneddylated huntingtin exon1 aggregates

Abstract: Selective autophagy of protein aggregates is necessary for maintaining the cellular proteostasis. Several regulatory proteins play critical roles in this process. Here, we report that the huntingtin interacting protein K (HYPK) modulates the autophagic degradation of poly-neddylated huntingtin exon1 aggregates. HYPK functions as a scaffolding protein that binds to the Nedd8 and LC3 proteins. The C-terminal ubiquitin-associated (UBA) domain of HYPK binds to the Nedd8, whereas an N-terminal tyrosine-type (Y-type… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 132 publications
(153 reference statements)
0
2
0
Order By: Relevance
“…Alternatively, the misfolding of the substrate we detect in our model protein may create a situation that favors the removal of the misfolded protein by the autophagy pathway. While a few recent reports have demonstrated proteasome-mediated degradation of NEDDylated substrates [ 47 , 48 , 49 ], there is less evidence in the literature that NEDDylated proteins can be degraded by autophagy [ 86 ]. Future work will have to carefully evaluate if autophagy-mediated degradation of naturally NEDDylated proteins occurs or if this is an artifact of the misfolded nature of the model substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, the misfolding of the substrate we detect in our model protein may create a situation that favors the removal of the misfolded protein by the autophagy pathway. While a few recent reports have demonstrated proteasome-mediated degradation of NEDDylated substrates [ 47 , 48 , 49 ], there is less evidence in the literature that NEDDylated proteins can be degraded by autophagy [ 86 ]. Future work will have to carefully evaluate if autophagy-mediated degradation of naturally NEDDylated proteins occurs or if this is an artifact of the misfolded nature of the model substrate.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed Ghosh et al have identified that the aggregate-prone form of Htt is NEDDylated and interacts with the UBA domain of huntingtin interacting protein K (HYPK). HYPK also interacts with the autophagy factor LC3 and together, induce the degradation of aggregated Huntington protein via the autophagy pathway [79]. Kim et al have recently shown that under stressful conditions which promote atypical NEDDylation in the cytoplasm, HDAC6 can directly interact with non-canonical targets of NEDDylation and induce aggregate formation [80].…”
Section: Protein Degradationmentioning
confidence: 99%